2020
DOI: 10.1101/2020.06.17.20133504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of SARS-CoV-2 infection from contaminated water systems

Abstract: Following the outbreak of severe acute respiratory syndrome coronavirus (SARS-CoV-2) in China, airborne water droplets (aerosols) have been identified as the main transmission route, although other transmission routes are likely to exist. We quantify SARS-CoV-2 virus survivability within water and the risk of infection posed by faecal contaminated water within 39 countries. We identify that the virus can remain stable within water for up to 25 days, and country specific relative risk of infection posed by faec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
0
26
0
4
Order By: Relevance
“…Finally, the assessment and appropriate treatment of wastewater is a measure that will be key in reducing the effect of sewage transmission of the virus into natural water systems. Specifically, Shutler et al (2020) outlines which countries pose the highest risk based on survival of the virus in wastewater. As such, high risk areas should act with caution and be attentive regarding how their wastewater is handled and treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the assessment and appropriate treatment of wastewater is a measure that will be key in reducing the effect of sewage transmission of the virus into natural water systems. Specifically, Shutler et al (2020) outlines which countries pose the highest risk based on survival of the virus in wastewater. As such, high risk areas should act with caution and be attentive regarding how their wastewater is handled and treated.…”
Section: Discussionmentioning
confidence: 99%
“… Casanova et al, 2009 found that in lake water, another coronavirus, mouse hepatitis virus (MHV), was stable for longer than 2 weeks. Finally, modelling studies by Shutler and colleagues that extrapolate infectivity from in vitro studies suggest that SARS-CoV-2 viral particle may be stable for up to ~25 days in warmer regions of the world ( Shutler et al, 2020 ). The study also predicted how differing environments around the world differ in relative risk of the virus in wastewater discharge ( Shutler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since COVID19 is a pandemic spread in 215 countries, it covers countries with wastewater treatment plants and other developing countries where wastewater is directly sent to the aquatic environment untreated. Thus, the presence of viable SARS-CoV-2 virus or RNA in aquatic environment is reported by several authors [ [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ].…”
Section: Spread Of Sars-cov-2 In the Environmentmentioning
confidence: 94%
“…Recently, Shutler [ 37 ], quantified the survival of SARS-COV-2 virus in some aquatic systems. Furthermore, it suggests that the SARS-CoV-2 virus can survive in untreated sewage systems and viral loads can be high, making it a potential route of fecal-oral transmission, the detection time is up to 25 days.…”
Section: Persistence Of Covid-19 (Sars-cov-2) In Aquatic Systemsmentioning
confidence: 99%